Modern Intellectual Discussions and Allama Shibli Nomani - Dr. Shahida Rasool; Dr. Zeenat Afshan; Baig, Muhammad Farooq (Zaban-o-Adab, 2022)
In the nineteenth century after the advent of colonialism in the subcontinent, the local intellectuals dispersed, especially the Muslims. Sir Syed Ahmad Khan and his companions advised Muslims to attach to modern learning. Shibli Nomani was impressed by Sir Syed’s ideas. He too became his admirer but his point of view was different in the sense that he wanted to instil the future in the bright past. He presented his own ideas in the light of the glorious past of the Muslims. In this essay, his personality has been discussed with respect to both aspects and specifically on his modern thoughts despite his liking for the past. Shibli Nomani, in general, is considered a religious leader but in this paper, it has been proved through his letters and literature that he accepted colonialism as well and asked the Muslims to do the same as Sir Syed Ahmad Khan taught them to.